Modelling familiarity : towards age-friendly exergame design - Zhang, Hao (Nanyang Technological University, 2020)
Older adults are suggested to take regular exercises to prevent themselves from serious health problems and complications. Although the benefits of taking physical exercises has been highly publicized, the majority of older adults do not achieve the minimum physical activity level. For alternative methods to deliver physical activities for older adults, literature has shown that exergames, with entertaining game graphics and tasks, can make the exercise more efficient and effective. However, due to the perceived complexity and difficulty of new technologies, referred to as the digital divide, it is sometimes difficult for older adults to voluntarily take up exergames or be engaged in exergame playing. Therefore, bridging such a digital divide is necessary for improving older adults' game experience and encouraging them to take regular exercise.